Impact of endometriosis on quality of life and psychological well-being - Salvatore Giovanni Vitale; Valentina Lucia La Rosa; Agnese Maria Chiara Rapisarda; Antonio Simone Laganà (Taylor & Francis Group, 2017)
The aim of this work is to propose a brief comment about the impact of endometriosis on quality of life and psychological well-being of women affected.